Low colonocyte folate is associated with uracil misincorporation and global DNA hypomethylation in human colorectum. - MOLLOY, ANNE (My University, 2013)
Low folate status is a risk factor for colon carcinogenesis; mechanisms proposed to account for this relationship include uracil misincorporation into DNA and global DNA hypomethylation. We investigated whether such biomarkers are related to folate status in isolated colonocytes from colonoscopy patients. In cases with adenomatous polyps (n = 40) or hyperplastic polyps (n = 16), colonocytes were isolated from biopsies from the polyp, from a site adjacent to the polyp, and from normal mucosa 10-15 cm distal to the polyp. In polyp-free controls (n = 53), biopsies were taken from ascending, transverse, and descending areas of colon. Within adenoma cases, there was a trend (P-trend < 0.001) of decreasing colonocyte folate (pg/10⁵ cells, mean ± CI) from the site distal to the polyp (16.9 ± 2.4), to the site adjacent to the polyp (14.7 ± 2.3), to the polyp (12.8 ± 2.0). Correspondingly, there were increases in uracil misincorporation (P-trend < 0.001) and global DNA hypomethylation (P-trend = 0.012) across the 3 sites. Colonocyte folate concentrations were significantly correlated with RBC folate concentrations, but only in individuals with generally lower (≤484 μg/L) RBC folate status (r = 0.54; P = 0.006; n = 24), and were also significantly lower in normal mucosa of cases with adenomatous polyps than in controls matched for colonic segment. In conclusion, localized folate deficiency in specific areas of colon might create carcinogenic fields and affect the development of colorectal polyps through uracil misincorporation and DNA hypomethylation; alternatively, the polyp itself might deplete folate in the surrounding tissue. Folate supplementation trials aimed at colon cancer prevention should target individuals with suboptimal folate status.
PUBLISHED
Keywords: Low folate status; Low folate status; Cancer